Strategies of Madrasah Principals in Internalizing Organizational Citizenship Behavior Based on Ihsan - Asbiri, Asbiri; Annur, Saipul; Karolina, Asri; Yuniar, Yuniar (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the strategies employed by the principal of the madrasah in fostering Organizational Citizenship Behavior (OCB) based on Ihsan, the forms of OCB exhibited by teachers and educational staff, and their contribution to the achievement of the vision of MTs Negeri 1 Ogan Komering Ulu. The study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation with the madrasah principal, teachers, and educational staff as the primary informants. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, and its validity was tested through triangulation of sources and techniques. The results of the study indicate that the madrasah principal’s strategies were implemented in a planned manner through the internalization of Ihsan values into the vision, madrasah culture, policies, and work programs. The implementation of these strategies is realized through exemplary leadership, the cultivation of religious activities, human resource empowerment, and the creation of a collaborative and spiritual work environment. The OCB behaviors of teachers and educational staff are reflected in the dimensions of altruism, conscientiousness, sportsmanship, courtesy, and civic virtue, driven by a sense of devotion and sincerity. This strategy positively contributes to the achievement of the madrasah’s vision through increased commitment, performance, and the strengthening of an Islamic work culture. This study confirms that Ihsan is the primary reinforcing factor in building sustainable OCB within the madrasah environment.